1.91 µm Passively continuous-wave mode-locked Tm:LiLuF4 laser. (December 2018) - Ling, Wei-Jun; Xia, Tao; Dong, Zhong; You, Liang-Fang; Zuo, Yin-Yan; Li, Ke; Liu, Qin; Lu, Fei-Ping; Zhao, Xiao-Long
Highlights: The first demonstration of continuous wave (CW) mode-locking in a Tm:LiLuF4 laser. By using the X-type cavity with extreme small laser mode, the absorbed pump threshold is low to 80mW. First investigated the absorption characters of Tm:LiLiF4 crystal in lasing and no lasing condition. A pair of CaF2 prisms is inserted into the cavity to compensate the intracavity dispersion and shorten the pulse duration.